1995
DOI: 10.1111/j.1532-5415.1995.tb07402.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychological Differentiation of Patients with Very Mild Alzheimer's Disease and/or Major Depression

Abstract: As efforts intensify to develop more powerful means to identify patients with Alzheimer's disease in its earliest stages, inclusion of specialist tests posing greater cognitive challenge than standard mental status scales has been one strategy. Our study explored how some of these neuropsychological tools behave psychometrically when analyzed on a single-case basis, and the results suggest a few are sensitive enough to boost detection above base rates alone while also being specific enough to reduce false alar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…[16][17][18][19][20] Although there are numerous tests for episodic memory, the KOLT is one that displays a normal distribution, shows no ceiling effect and has high sensitivity and specificity in the detection of mild Alzheimer's disease. 30 A limitation of this study is the lack of longitudinal data on cognition. Studies on APOE4 in elderly people may be affected by selective mortality, but the allelic frequency in our study was still around 18%, compared with nearly 20% in a Norwegian population study.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18][19][20] Although there are numerous tests for episodic memory, the KOLT is one that displays a normal distribution, shows no ceiling effect and has high sensitivity and specificity in the detection of mild Alzheimer's disease. 30 A limitation of this study is the lack of longitudinal data on cognition. Studies on APOE4 in elderly people may be affected by selective mortality, but the allelic frequency in our study was still around 18%, compared with nearly 20% in a Norwegian population study.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…The KOLT has been validated for the detection of both mental impairment in old age 29 and mild Alzheimer's disease. 30 It has been widely used in Norway for 20 years.…”
Section: Cognitive Testingmentioning
confidence: 99%
“…However, there are reports indicating that both immediate and delayed measures of memory can be employed to discriminate between AD patients and depressive patients (Desrosiers et al, 1995;Jones et al, 1992). In fact, a recent review by Wright & Persad (2007) reported that depressed patients are generally unimpaired in their ability to retain learned information and suggested that the differential diagnosis of AD patients should include visual recognition and visual-construction tasks.…”
Section: Differential Nvm Deficits In the Ad And Ud Groupsmentioning
confidence: 97%
“…Despite the fact that several studies have focused on NVM deficits in UD patients (for a review, see Cassens, Wolfe, & Zola, 1990), particularly on how complex visuospatial recognition and visual recall are impaired in UD (Beats, Sahakian, & Levy, 1996;Butters et al, 2004;ElderkinThompson et al, 2004;Elliot et al, 1996;Sweeney, Kmiec, & Kupfer, 2000), the extent of sensitivity of NVM tests as instruments for discriminating AD from UD is almost unknown (La Rue, D'Elia, Clark, Spar, & Jarvik, 1986;Swainson et al, 2001). The problem is compounded by the fact that NVM tasks vary considerably from study to study (Desrosiers, Hodges, & Berrios, 1995;Jones et al, 1992;Shuttleworth & Huber, 1989). For instance, previous studies have employed various types of stimuli, such as geometric figures or abstract designs, depending on the different criteria used for NVM test construction (for a review, see Moye, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…When memory performance was compared between groups of patients with different brain disorders by means of the SRP, no differential deficits were found with the SRP scores, although differential memory deficits have been described with other memory tests (e.g. depression vs. dementia [27][28][29]; Alzheimer vs. multi-infarct dementia [26]). …”
Section: Discussionmentioning
confidence: 99%